2008
DOI: 10.1007/s00191-008-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

The outsourcing productivity paradox: total outsourcing, organisational innovation, and long run productivity growth

Abstract: A growing number of empirical studies find a relationship between the outsourcing of activities and a long term loss of firm productivity growth. The paper addresses this outsourcing productivity paradox by examining the connection between total outsourcing and organisational innovation. We present a model of organisational innovation in which managers raise productive efficiency by identifying organisational architectures that more effectively integrate value-adding activities and administrative routines. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 50 publications
0
38
0
1
Order By: Relevance
“…This result is not completely new in the literature, as already discussed in Section 1, and can be explained by the management underestimation of costs connected to outsourcing itself and to the necessity to reorganise the firm activities once the firm begins to outsource (Görzig & Stephan, 2002;Ito et al, 2010). Moreover the loss of control on production activities under total outsourcing may restrict a firm's capability to engage in organisation innovation and restructuring (Windrum et al, 2009) The results obtained from the different specifications do not alter the main conclusions. The sign and the significance of the coefficients of the covariates are the same for all of the sets of estimates, although there are certain differences in the values of the estimated coefficients of outsourcing intensity.…”
Section: The Productivity Effect Of Outsourcingmentioning
confidence: 98%
See 2 more Smart Citations
“…This result is not completely new in the literature, as already discussed in Section 1, and can be explained by the management underestimation of costs connected to outsourcing itself and to the necessity to reorganise the firm activities once the firm begins to outsource (Görzig & Stephan, 2002;Ito et al, 2010). Moreover the loss of control on production activities under total outsourcing may restrict a firm's capability to engage in organisation innovation and restructuring (Windrum et al, 2009) The results obtained from the different specifications do not alter the main conclusions. The sign and the significance of the coefficients of the covariates are the same for all of the sets of estimates, although there are certain differences in the values of the estimated coefficients of outsourcing intensity.…”
Section: The Productivity Effect Of Outsourcingmentioning
confidence: 98%
“…The sign and the size of the effect of outsourcing on productivity (and profitability) at the level of the firm therefore can only be revealed by empirical studies. A detailed description of the causes and effects of outsourcing can be found, for example, in Bengtsson and Dabhilkar (2009) and Windrum at al. (2009).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Bartel et al (2008) have shown that outsourcing activities are more advantageous for a service firm when the technological changes are evolving rapidly. Windrum et al (2009) have focused on the paradox of outsourcing productivity by examining the links between total outsourcing and operational innovation. They have shown that, on the short term, the 'outsourcing' firms are willing to decrease their marginal production costs.…”
Section: Context and Definitionsmentioning
confidence: 99%
“…Windrum et al (2009) propose an interesting alternative explanation for the outsourcingproductivity paradox, which links the outsourcing decision to organizational change. Relying on the modular theory of the firm, they argue that the positive effects of total outsourcing on productivity growth materialize only after managers have identified the organizational architectures that most efficiently combine the externalities from value-adding activities such as research and development (R&D), design, production and marketing.…”
Section: Introductionmentioning
confidence: 99%